STRATEGI GURU MENGATASI KESULITAN PESERTA DIDIK DALAM PEMBELAJARAN TAHFIDZUL QUR’AN JUZ 30 DI SEKOLAH DASAR ISLAM TERPADU (SDIT) PERSIS KOTA PALU - Dhani, Ria Novia; Gunawan B. Dulumina; Fikri Hamdani (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2024)
The implementation of Tahfidzul Qur'an learning at SDIT Persis, Palu City lasted for two hours face to face using two systems, namely Muraja'ah and adding new memorization (ziyadah). 2) In learning Tahfidzul Qur'an juz 30 at SDIT Persis there are difficulties for students in the learning process including reading the Al-Qur'an, difficulty distinguishing similar verses, lack of doing muraja'ah, time factors, the influence of cellphones, and level of ability different students. 3) strategies applied by teachers to overcome difficulties in learning Tahfidzul Qur'an, namely interspersing learning the science of Tajweed in each Tahfidz lesson, emphasizing the differences in the next verse, optimizing muraja'ah activities before depositing additional memorization, teaching how to manage time, prohibiting bringing cellphones to school and give support.